Investigation of Commitment Level of Safety Factor in Construction Industry at Kuala Lumpur, Malaysia - Badrul Hisham, Farah Afiqah; Nagapan, Sasitharan (Recent Trends in Civil Engineering and Built Environment, 2024)
The construction industry in Kuala Lumpur, Malaysia has seen a record of rapid growth every years but the development is slowing down with the number of accidents that occur due to lack of attention to safety aspects at construction sites. Commitment to safety is critical to improving safety performance, but less obvious is the nature of safety commitment at the individual employee level. Therefore, this study focuses on the commitment level of safety factors by the parties involved in the construction industry such as the project manager, safety officer, site supervisor and laborer. The research methodology includes quantitative approach and the data has been collected from questionnaire survey. SPSS version 26 has been used to analyze the Cronbach's Alpha for reliability test, frequency and descriptive analysis and also Likert scaling along with the mean score to present the data resulted. Accordingly, the primary safety factor in construction industry was maintained safe work condition and workers are committed with wearing personal protective equipment (PPE) on construction sites. The result of this research was to benefits parties involved in construction industry by improving the level of safety commitment and raise awareness about safety.